2019
DOI: 10.1002/ptr.6473
|View full text |Cite
|
Sign up to set email alerts
|

Moringa oleiferaand glycemic control: A review of current evidence and possible mechanisms

Abstract: Maintaining glycemic control in diabetes and prediabetes is necessary to prevent many health complications and mortality. Although different hypoglycemic drugs are used for this purpose, there is still a growing interest in the use of medicinal plants due to their low price, easy availability, and fewer or no side effects. Moringa (Moringa oleifera Lam.) is a medicinal plant that has been traditionally used in the management of diabetes. This review aims to present the existing literature published until Febru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 38 publications
1
37
0
7
Order By: Relevance
“…Although beneficial effects of M. oleifera phytochemicals in reducing the risk of chronic diseases have been shown through various in-vitro/in-vivo studies [ 30 ], much more metabolic evidence is required to define a particular target(s) where the phytochemicals act as a modulator (inhibitor or activator) of diverse cellular pathways or specific enzymes. The proposed mechanisms for reducing glycemia by M. oleifera include inhibition of digestive enzymes and glucose uptake from the intestine, increased insulin secretion and sensitivity in diverse tissues, cytoprotective indirect antioxidant activity, and decreased gluconeogenesis in the liver [ 31 ]. However, evidence regarding changes in antioxidant enzymes due to M. oleifera are ambiguous because activities reported in literature vary significantly depending on the experimental conditions and remain poorly understood in animal studies [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although beneficial effects of M. oleifera phytochemicals in reducing the risk of chronic diseases have been shown through various in-vitro/in-vivo studies [ 30 ], much more metabolic evidence is required to define a particular target(s) where the phytochemicals act as a modulator (inhibitor or activator) of diverse cellular pathways or specific enzymes. The proposed mechanisms for reducing glycemia by M. oleifera include inhibition of digestive enzymes and glucose uptake from the intestine, increased insulin secretion and sensitivity in diverse tissues, cytoprotective indirect antioxidant activity, and decreased gluconeogenesis in the liver [ 31 ]. However, evidence regarding changes in antioxidant enzymes due to M. oleifera are ambiguous because activities reported in literature vary significantly depending on the experimental conditions and remain poorly understood in animal studies [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Especially important, given the high NCD (particularly diabetes) rates in the Pacific and northern Australia, are the anti-diabetes and anti-cardiovascular disease effects of most of the plants featured in the factsheets, demonstrated in scientific studies. Studies with evidence for this include the following: drumstick [ 36 , 37 , 38 , 50 , 60 ], amaranth [ 61 , 62 , 63 ], bele [ 64 , 65 , 66 ], chilli [ 67 , 68 , 69 ], purslane [ 70 , 71 , 72 ], kangkong [ 73 , 74 , 75 ], ofenga [ 76 , 77 , 78 ], hedge panax [ 79 , 80 ], chaya [ 39 , 40 ], pumpkin [ 81 , 82 ], and choko [ 83 , 84 ]. Their inclusion in the diet in sufficient quantity is likely to reduce the risk of diabetes and cardiovascular disease, not only by reducing glycemic load when they are included with high-carbohydrate meals, but also because of specific anti-diabetes effects.…”
Section: Resultsmentioning
confidence: 99%
“…Others, notably lutein (which is usually abundant in leafy vegetables) and zeaxanthin are important for eye health and can reduce the risk of cataracts [35]. Importantly, given the current NCD pandemic, there is growing evidence for specific activity of certain plants against diabetes and cardiovascular disease, e.g., drumstick [36][37][38] and chaya [39,40].…”
Section: Why Leafy Plants?mentioning
confidence: 99%
“…29 This decrease in blood glucose level could be attributed to some level of in vivo inhibition against αamylase and α-glucosidase resulting in a suppression of hyperglycemia. 30 The ANOVA test shows the significant value of 0.017, so it can be concluded that there is a significant difference (p < 0.05) between the treatments given. The Student Newman Keuls (SNK) test in Table 3 shows the best inhibitory activity was demonstrated by dose combination 2 and this combinations gave better inhibitory activity than the positive control (acarbose).…”
Section: Blood Glucose Level Reduction Using In Vivo Assaymentioning
confidence: 94%